2013
DOI: 10.1177/1527154413485901
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Political Astuteness Following Nurse Legislative Day

Abstract: Political astuteness, including awareness, knowledge, and involvement, is necessary if nurses are to engage in policy advocacy-a vital aspect of the nursing profession. However, little is known about the effects of learning activities, such as legislative days, on political astuteness. The purpose of this research was to determine if political astuteness changed after participants attended a state nurse legislative day. Pre and post data were collected from participants in two studies (N = 80 and N = 34) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…Other articles utilized an established instrument to examine the degree of policy astuteness of those surveyed (Byrd et al. ; Primomo ; Primomo & Björling ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other articles utilized an established instrument to examine the degree of policy astuteness of those surveyed (Byrd et al. ; Primomo ; Primomo & Björling ).…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, several authors, for example, Cohen & Milone-Nuzzo (2001), Wilson (2002) and Arabi (2014), tested existing models of policy influence. Other articles utilized an established instrument to examine the degree of policy astuteness of those surveyed (Byrd et al 2012;Primomo 2007;Primomo & Bj€ orling 2013).…”
Section: Study Designs and Focusmentioning
confidence: 99%
“…Empirical research has found that managers use politics for constructive organizational and social purposes (e.g., Perrewé et al 2007;Buchanan 2008;Primomo and Björling 2013), including creating and discerning public value (Hartley et al 2015). Public managers often have to cross the line so that the politics/administration dichotomy is not a line but a zone in some contexts (Svara 2001;Alford et al 2017).…”
Section: Political Astutenessmentioning
confidence: 99%
“…Public managers often have to cross the line so that the politics/administration dichotomy is not a line but a zone in some contexts (Svara 2001;Alford et al 2017). Public managers say they are more effective in working with elected/appointed politicians when they are politically astute (e.g., Svara 2001;Manzie and Hartley 2013;Primomo and Björling 2013;Alford et al 2017).…”
Section: Political Astutenessmentioning
confidence: 99%
“…[8][9][10] In addition, the legislative fellowship provides students exposure to a broad array of state officials, policy makers, district constituents, lobbyists, advocacy groups, and leaders of professional organizations. [11][12][13][14][15] There are several foundational aspects of legislative fellowships that faculty should be aware of to create successful fellowships. Key to creation of such fellowships is that nursing faculty must first identify legislators who are willing to sponsor fellowships.…”
Section: Development Of the Legislative Fellowshipmentioning
confidence: 99%